Fibrocyte enrichment and myofibroblastic adaptation causes nucleus pulposus fibrosis and associates with disc degeneration severity - Yi Sun; Yan Peng; Zezhuo Su; Kyle, K. H. So; Qiuji Lu; Maojiang Lyu; Jianwei Zuo; Yongcan Huang; Zhiping Guan; Kenneth M. C. Cheung; Zhaomin Zheng; Xintao Zhang; et al. (Bone Research)
Abstract Fibrotic remodeling of nucleus pulposus (NP) leads to structural and mechanical anomalies of intervertebral discs that prone to degeneration, leading to low back pain incidence and disability. Emergence of fibroblastic cells in disc degeneration has been reported, yet their nature and origin remain elusive. In this study, we performed an integrative analysis of multiple single-cell RNA sequencing datasets to interrogate the cellular heterogeneity and fibroblast-like entities in degenerative human NP specimens. We found that disc degeneration severity is associated with an enrichment of fibrocyte phenotype, characterized by CD45 and collagen I dual positivity, and expression of myofibroblast marker α-smooth muscle actin. Refined clustering and classification distinguished the fibrocyte-like populations as subtypes in the NP cells - and immunocytes-clusters, expressing disc degeneration markers HTRA1 and ANGPTL4 and genes related to response to TGF-β. In injury-induced mouse disc degeneration model, fibrocytes were found recruited into the NP undergoing fibrosis and adopted a myofibroblast phenotype. Depleting the fibrocytes in CD11b-DTR mice in which myeloid-derived lineages were ablated by diphtheria toxin could markedly attenuate fibrous modeling and myofibroblast formation in the NP of the degenerative discs, and prevent disc height loss and histomorphological abnormalities. Marker analysis supports that disc degeneration progression is dependent on a function of CD45+COL1A1+ and αSMA+ cells. Our findings reveal that myeloid-derived fibrocytes play a pivotal role in NP fibrosis and may therefore be a target for modifying disc degeneration and promoting its repair.